Neurocognitive performance in children aged 6 to 16 with attention-deficit/hyperactivity disorder without medication - Fernandez-Arana, Alberto (2026)
Objective: To characterize the neurocognitive profile of children with Attention-Deficit/Hyperactivity Disorder (ADHD) and to identify potential performance differences according to sex. Methods: 344 children aged 6–16 years (160 girls and 184 boys) diagnosed with ADHD and examined with the Evaluación Neuropsicológica Infantil version 2 (ENI-2) battery were included. Results: In the domain of information encoding and memory, children exhibited low performance in both auditory-verbal and visual memory tasks, affecting both encoding and delayed recall, as well as in the complex figure copy task. Girls outperformed boys in verbal tasks and in the simple figure copy. In the domain of language and phonological processing, low performance was observed in syllable and pseudoword writing accuracy, phonemic perceptual skills, silent reading comprehension, word reading accuracy, and metalinguistic skills, with a female advantage in word writing and phonemic abilities. In oral comprehension and production, lower performance was found in silent reading speed and right–left spatial comprehension, whereas higher performance was observed in sentence writing accuracy and oral reading; girls showed superior performance in sentence writing. In verbal fluency and lexical access, performance was low in cancellation tasks and in both phonemic and semantic fluency, with girls showing better performance in the latter. Conclusion: Children with ADHD showed consistent patterns of poor cognitive performance and gender differences. Understanding these characteristics could guide more individualized and effective interventions.